Detection of antibiotic resistant bacteria on hands and mobile phones - Danen, Ana Petronella Vasconcelos (2015)
Mobile phones are daily used and in a frequent manner. There is no awareness in the general public of their potential to be a reservoir of specific bacteria. The use of touch screen mobile phones is exponentially growing and the hospital outbreaks with touch screens as contamination source is more frequently being registered. Touch screens are not perceived as a method of transmission of potentially pathogenic and antibiotic resistant bacteria, thus posing as a health risk due to being overlooked in terms of disinfection standards in healthcare settings. Bacteria are acquiring resistance to various antibiotics, possibly becoming multiresistant such as HA-MRSA. This poses a public health risk when faced with the possibility that these bacteria can adhere and remain on mobile phones over a great length of time. These devices may serve as vector of transmitting bacteria to their owners and third parties. This is even more preoccupying when individuals are healthcare professionals. This study aimed to identify and quantify the bacteria present on mobile phones and the hands of their users. The bacteria were submitted to antibiotic screening and MRSA were selected and genotypically characterized, and the SCCmec element typified. Bacillus spp. was detected in 7.5% of the individuals and in 28% of the mobile phones, hemolytic bacteria were detected in 82% of the individuals, Staphylococcus spp. in 96.5%, S. aureus in 82%, Enterobacteriaceae in 1% and MRSA in 6%. Erythromycin resistance in staphylococci was verified to be 44.7% in general. Oxacillin and Clindamycin resistance was 12.5% and 9.8%, respectively. 0.8% of the screened bacteria were multiresistant, and 3.3% of the individuals presented multiresistant bacteria on their hands. Four samples were identified as being MRSA, all multiresistant and from those, two samples were presumptively identified as SCCmec type II and SCCmec type III, both HA-MRSA. Male individuals have "dirtier" hands than female students in terms of potential pathogenic bacteria. Various factors such as, keyboard type, hand and mobile phone hygiene, nail length, manicure type and presence, taking device to the bathroom, owning pets and hand washing have influence on the bacterial count of the hands. Mobile phones can serve as reservoirs of specific bacterial that may be pathogenic and multiresistant to antibiotics, and should be publically perceived as a possible contamination source.